Small intestinal flukes of the genus Metagonimus (Digenea: Heterophyidae) in Europe and the Middle East: A review of parasites with zoonotic potential - Scholz, Tomáš; Kuchta, Roman; Barčák, Daniel; Cech, Gábor; Oros, Mikuláš (Parasite (Paris, France), 2024)
The heterophyid trematode Metagonimus romanicus (Ciurea, 1915) (Digenea) is redescribed on the basis of type material from domestic dogs (Canis familiaris) in Romania, vouchers from experimentally infected cats (Felis catus) and adults recovered from golden hamsters (Mesocricetus auratus) infected with metacercariae from scales of chub (Squalius cephalus) and common nase (Chondrostoma nasus) (Cypriniformes: Leuciscidae) in Hungary. This trematode, endemic to Europe and neighbouring regions (northwestern Türkiye), was previously misidentified as M. yokogawai (Katsurada, 1912), a zoonotic parasite of humans in East Asia. However, the two species differ considerably both genetically and morphologically, e.g., in the position of the ventral sucker, the presence of the prepharynx, the anterior extent of the vitelline follicles and the posterior extent of the uterus. Metagonimus ciureanus (Witenberg, 1929) (syn. Dexiogonimus ciureanus Witenberg, 1929), described from domestic cats and dogs in Israel, is a valid species distributed in the Middle East and Transcaucasia, which is also confirmed by molecular data. It differs from all Metagonimus species, including M. romanicus, in having symmetrical testes instead of the oblique testes of the other congeners. The zoonotic significance of M. romanicus and M. ciureanus is unclear, but appears to be low in Europe, mainly because raw or undercooked, whole fish with scales are generally not consumed. Accidental infection of fishermen by metacercariae in the scales when cleaning fish is more likely, but has never been reported. Remains of cyprinoids with scales infected with metacercariae of Metagonimus spp. can be an important natural source of infection for dogs, cats, and other carnivores, which can serve as a reservoir for these parasites.
Keywords: Genotyping; psi; Metacercariae; Taxonomy; Fish-borne zoonoses; Redescription; kočky; Humans; Dogs; Střední východ; Heterophyidae; Trematoda; metacerkárie; Female; Middle East; Trematode Infections; infekce červy třídy Trematoda; lidé; Parasites; zvířata; Europe; křeček rodu Mesocricetus; Mesocricetus; ženské pohlaví; Palaearctic region; Cats; Animals; SEM; Evropa; paraziti; Cyprinidae